Pandangan Mahasiswa Terhadap Muslimah Bercadar Di Fakultas Ushuluddin Dan Studi Islam Uin Sumatrera Utara - Muhammad Ariq Fadil Sobri; Asiska Nadia Hasibuan; Talitha Ivana Augie; Miftah Fauzan Azimah; Muhammad Irfan Prayandy (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
The use of the veil at the Ushuluddin Faculty is analyzed as a religious practice that involves factors such as religious teachings, environment, and personal motivation. The factor of religious teachings is the main driver, with female students viewing the veil as a religious commandment that must be obeyed as a form of devotion to Allah. The Koran instructs Muslim women to wear the hijab by wearing a headscarf that can cover their head and chest, but there are different opinions regarding this. the verse. The proposed research method involves interviews and literature searches with a qualitative approach. The aim of this research is to analyze the opinions of ulama regarding Surah Al-Ahzab verse 59 and analyze the community's views regarding the veil and hijab at the Ushuluddin Faculty. As for students' views regarding the veil and hijab , some of them can accept the existence of women who wear the veil, and there are several groups of people who cannot accept women who wear the veil, because those who wear the veil close themselves off from society and are reluctant to interact with the social environment.